Acid‐activated spent bleaching earth as a sorbent for chromium (vi) in aqueous solution - Low, K.S.; Lee, C.K.; Lee, T.S. (Informa UK Limited, 2003)
Spent bleaching earth, an industrial waste produced after the bleaching of crude palm oil, was investigated for its potential in removing Cr(VI) from aqueous solution. The earth was treated with different amounts of sulfuric acid and under different activation temperatures. Results show that the optimum treatment process involved 10% sulfuric acid at 350° C. The effects of contact time, pH, initial concentration, sorbent dosage, temperature, sorption isotherms and the presence of other anions on its sorption capacity were studied. Isotherm data could be fitted into a modified Langmuir isotherm model implying monolayer coverage of Cr(VI) on acid activated spent bleaching earth. The maximum sorption capacity derived from the Langmuir isotherm was 21.2 mg g‐1. This value was compared with those of some other low cost sorbents. Studies of anion effect on the uptake of Cr(VI) on acid activated spent bleaching earth provided the following order of suppression: EDTA >PO43‐>SSO42‐ >NO3>Cl‐.